Evasão no curso de Ciências Contábeis da UFRN: perfil e trajetória acadêmica dos estudantes evadidos e a sua relação com os processos seletivos (Vestibular e SiSU) - Carvalho, Daniele da Rocha (2022)
The changes that have taken place in society since the second half of the 20th century have demanded several transformations in the social, economic and political fields. As a result of globalization and the development of communication and information technologies, today's society, "known as the knowledge society", began to demand a new generation of workers with new standards of competence, with the need for changes in the higher education system. The neoliberal policies for education, implemented in Brazil since the 1990s, focused on the reduction of resources for education, prioritized the expansion in private and diversified institutions, which provided the massification of higher education, bringing several problems, among which the increase in the dropout rate and the prolongation of stay in the course. These problems have been getting worse since the 2000s, due to the change in the selection process for admission to Higher Education Institutions (IES). In this context, in order to make admission to higher education more flexible, Brazilian educational policies have diversified the forms of admission, including the Unified Selection System (SiSU) which replaced the admission process in IFES from 2010, starting to use the adjustment of vacancies in undergraduate courses. The general objective of the thesis was to analyze the changes that occurred in the profile and trajectory of students who dropped out of the Accounting Sciences course, establishing a relationship with the form of admission to UFRN, vestibular (2013.1) and ENEM/SiSU (2013.2). The theoretical-methodological framework used a qualitative approach. As for the procedures and techniques of data collection, document analysis and the application of questionnaires were used to all dropouts from the Accounting Sciences Course at UFRN who entered in 2013. To complement the information, interviews were used with a non-probabilistic sample composed of dropout students entering the two selection processes. For data analysis, historical series were prepared using quantitative data and content analysis for a better understanding of the subjects' interviews. We found that the number of students who dropped out during the entrance examination period (2013.1) was 28 students, while during the ENEM/SiSU selection process (2013.2) it was 51 students, resulting in an increase of 82.14% when comparing the two periods. There was also a change in the profile of dropouts, which showed an increase in the percentage of single students, as well as a considerable increase in female dropouts. Another characteristic to be highlighted in the change in the process is that the dropouts who entered through ENEM/SiSU were already graduated or were already students of other courses when they entered the Accounting Sciences course at UFRN. With regard to ENEM/SiSU, mobility has become a factor that has contributed to dropout. There was an increase in the percentage of dropouts, both among quota students and among those with broad competition, influenced by the student's own socioeconomic context and by the grade obtained in the ENEM. It was also evident in the study that the factors that most influenced the trajectory of the dropout students who entered the ENEM/SiSU were the problems associated with the teaching-learning process, the pedagogical practices used by the teachers, the nonadaptation to the course and the aspiration for another course, while the reasons that most influenced the dropouts entering the entrance exam were the need to work, time to reconcile study and work, mobility, among others. Finally, it is concluded that there is a need to review the ENEM/SiSU operating policy, regarding the choice of course, ensuring a better fit between the students' interests and the choice of profession.